Pre- and Posttreatment MR Imaging in AIDS-Related Kaposi Sarcoma of the Conjunctiva and Lacrimal Gland - Scheschonka, A.; Mösch, M.; Krieglsteiner, S.; Turowski, B.; Zanella, F. E. (American Journal of Neuroradiology, 2003)
Summary: AIDS-related Kaposi sarcoma can affect the eye: the (bulbar) conjunctiva and lacrimal gland being rare sites of occurrence. We present a case of AIDS-related Kaposi sarcoma of the conjunctiva in which MR imaging was effective in suggesting the diagnosis and aiding therapeutic strategy. We also discuss advances in imaging of ocular and orbital malignancies presented in the recent literature.